Social work with drug, alcohol and substance misusers - Goodman, Anthony (Anthony Harvey) (2013)
It has long been recognised that clients with addiction problems need a skilled and thoughtful response when they come into contact with social services. This new edition will help students to cultivate these skills with sections on anti-oppressive practice and a focus on service user empowerment. Case studies and reflective exercise will focus the student on this holistic approach while underpinning key learning objectives. With a new focus on social work practice with alcohol misusers, this third edition provides a firm foundation for the skills required when working with people with drug and substance addictions.
Machine generated contents note: 1. The links between social work practice and working with substance-misusing clients -- 2. The nature and extent of drug taking in the United Kingdom -- 3. The history, legislative changes and key policy documents involved in the field of substance misuse -- 4. What is known about drug misusers and drug offenders and the drugs commonly used? -- 5. Policy changes and substance misuse -- 6. Developments since the change to a coalition government and the problems of alcohol -- 7. Professional practice issues and approaches -- 8. Conclusion.
Includes bibliographical references (pages 149-159) and index.
Keywords: Social work with drug addicts -- Great Britain; Drug addicts -- Services for -- Great Britain; Substance abuse -- Treatment -- Great Britain; Substance-Related Disorders -- therapy; Social Work; Drug addicts -- Services for; Social work with drug addicts; Substance abuse -- Treatment; Great Britain